Aspek Yang Mempengaruhi Kualitas Informasi Laporan Keuangan - M Sulkhanul Umam; Rahandhika Ivan Adyaksana; Tantri Dyah Ayu Lestari (InFestasi, 2024)
The hotel industry is needed to significantly increase welfare and economic recovery after COVID-19. The high growth of the hotel industry must be balanced with quality financial management and reporting because many parties use financial reports as a basis for decision-making. The research examined the influence of accounting understanding, utilization of information technology, internal control systems, and human resource competency on the quality of financial statements. This research uses a quantitative approach with questionnaire tools distributed to 56 hotels with 4-star and 5-star hotel classifications. The research results show that understanding accounting, information technology utilization, internal control systems, and human resource competency influence the quality of financial statements. Fulfillment of the elements can be achieved by an adequate understanding of accounting from the personnel who prepare financial reports, the use of technology used by the company to increase the accuracy and availability of reports, a control system to minimize fraud, and competent human resources so that the rules present reports.